A German version of the Caregiver Skills scale for caregivers of patients with anorexia nervosa. (17th December 2020) - Zeiler, Michael; Philipp, Julia; Truttmann, Stefanie; Wittek, Tanja; Franta, Claudia; Imgart, Hartmut; Zanko, Annika; Auer‐Welsbach, Ellen; Kahlenberg, Leonie; Wagner, Gudrun; Karwautz, Andreas
Abstract: Objective: To investigate acceptance, reliability, convergent validity, factor structure and sensitivity to change of a German translation of the Caregiver Skills (CASK) scale measuring skills related to caring for patients with eating disorders. Methods: Two hundred and thirty‐three parents (76% female) of adolescent patients (mean age 15.1) with anorexia nervosa (AN) completed the 27 items of the CASK. We calculated item/scale characteristics, internal consistencies and bivariate correlations with other measures of caregiving burden. We evaluated goodness‐of‐fit of the 6‐factor model using confirmatory factors analysis and explored the sensitivity to change following two skills‐based trainings. Results: The fit of the 6‐factor model was acceptable (Root Mean Square Error of Approximation: 0.077, Standard Root Mean Square Residual: 0.080). Cronbach's alpha was excellent for the total (.94) and acceptable for all subscales (0.73–0.85). The total CASK score was 68.04 (max. 100) showing relatively high self‐rated caregiver skills. Non‐completion rates of most items were low (<3%) indicating high acceptance. Convergent validity was found with measures of psychological distress, depression, anxiety and expressed emotion. The total score significantly increased following an 8‐week workshop/online skills training ( d  = 0.70) and a 2‐day multi‐family intervention ( d  = 0.47). Discussion: The German CASK version is a useful instrument to assess caregiver skills in parents of patients with AN and to evaluate outcomes of skills‐based trainings. Key points: This study provides the first translation and evaluation of a German version of the Caregiver's skills scale (CASK) The CASK showed high acceptance across caregivers, good internal consistencies of the total and subscales and acceptable fit of the 6‐factor model Caregiver's skills as measured with the CASK improved with medium‐to‐high effect sizes following skill‐based training/multi‐family therapy based on the cognitive interpersonal maintenance model of eating disorders